DAGUSIBU education to improve community understanding of medication management in Kalibaru Village, Cirebon Regency - Senja, Rima Yulia; Sulastri, Lela; Supriyadi, Yadi; Maulidiyani, Roqmah; Nuraisah, Alvia; Ayu, Intan; Rahmadina, Putri; Ananda, Rega; Cahyani, Mufida; Dimas, Gilang (Community Empowerment, 2025)
DAGUSIBU is a family-based movement program aimed at raising awareness and understanding of the proper use and management of medicines. This community service program was conducted in Kalibaru Village, Tengah Tani District, Cirebon Regency, with the objective of enhancing public knowledge and awareness regarding medication management within the household. The DAGUSIBU educational method was implemented through presentations, educational video screenings, hands-on practice in handling damaged or expired medicines, and activity evaluations. The results showed a significant increase in public knowledge after the educational activities were conducted. Awareness of obtaining medicines from official facilities increased by 82.63%, proper medication usage improved by 84.14%, correct medication storage knowledge rose by 89.44%, and understanding of handling damaged and expired medicines increased by 76.8%. Through this educational initiative, the community became more selective in acquiring, using, storing, and disposing of medicines, thereby supporting therapy optimization and the rational use and management of medications.